ASUHAN KEPERAWATAN PADA KLIEN TUBERKULOSIS PARU (TB PARU) DENGAN BERSIHAN JALAN NAFAS TIDAK EFEKTIF - Fina Afyanita (2023)
Tuberculosis (pulmonary TB) is an infectious disease caused by the bacterium Mycobacterium tuberculosis which mainly attacks the lungs but can attack other organs. The main symptom of patients with pulmonary tuberculosis is cough with sputum for a minimum of 2 weeks. Cough can be accompanied by other indications, such as sputum mixed with blood, coughing up blood, feeling unwell, lethargic, short of breath, depreciating body weight, loss of desire to eat and night sweats without physical activity. The research design used was a case study and this type of research was used in the form case study. This case study is a case study related to medical surgical nursing which focuses on Tuberculosis (Pulmonary TB) cases in the Catelya Room of the Tresna Werdha Budi Mulia 1 Cipayung Social Institution, the method used is the nursing system which includes nursing assessment, nursing diagnosis, nursing intervention, implementation and nursing evaluation. The problems that arise in the case are a. Ineffective airway clearance is related to airway hypersecretion/retained secretions (IDHS, D.0149, page 18), Nutrition Deficits are related to Increased Metabolic Requirements (SDKI, D.0019, page 56) and Knowledge deficits are related to less exposure to information (SDKI, D. 0111, page 246). after carrying out nursing actions for 3x24 hours the evaluation results of all nursing diagnoses are resolved in accordance with the objectives of the established outcome criteria. The application of nursing care to pulmonary tuberculosis clients achieves the expected results due to good cooperation between clients and nurses